1963
DOI: 10.1021/jm00339a012
|View full text |Cite
|
Sign up to set email alerts
|

Hypotensive 1,2,4-Benzothiadiazines

Abstract: 3,4-dimethyl-5-phenyloxazolidine (X).41-A 7.0 g. sample (0.0425 mole) of tff-ephedrine30 was cyclized with cyanogen bromide using Method A. After recrystallization from etherpetroleum ether, 4.77 g. (50.5%) of pure 2-imino-3,4-dimethyl-5phenvl-2-oxazolidine (X) was obtained, m.p. 67-71 °. Literature41' m.p.'71-73°: )£% 3

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

1966
1966
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…3,5-Bis(N-(4,6-dimethyl-7-ethylaminocoumarin)methyl)phenol, 5, was synthesized as described. [10] Commercially available [Ru-(bpy) 3 ]Cl 2´6 H 2 O (Aldrich) was converted into the corresponding PF 6 À salt by metathesis with NH 4 PF 6 (Aldrich) in water. Reversed-phase HPLC (C18, semi-preparative) was performed with a Waters HPLC system equipped with a diode array absorption detector.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…3,5-Bis(N-(4,6-dimethyl-7-ethylaminocoumarin)methyl)phenol, 5, was synthesized as described. [10] Commercially available [Ru-(bpy) 3 ]Cl 2´6 H 2 O (Aldrich) was converted into the corresponding PF 6 À salt by metathesis with NH 4 PF 6 (Aldrich) in water. Reversed-phase HPLC (C18, semi-preparative) was performed with a Waters HPLC system equipped with a diode array absorption detector.…”
Section: Methodsmentioning
confidence: 99%
“…WILEY states are especially intriguing because of their outstanding photochemical, photophysical, and electrochemical properties. [6] In this regard, many large polynuclear dendritic arrays of MLCT complexes have been synthesized and their photophysical and electrochemical properties generally display novel characteristics. [7] Very recently, it has been reported that a single [Ru(bpy) 3 ] 2 core (bpy 2,2'-bipyridine) can be tethered to a well defined array of benzyl, 4'-tert-butylphenyloxy, or naphthyl peripheral units.…”
Section: First Generation Light-harvesting Dendrimers With a [Ru(bpy)mentioning
confidence: 99%
See 1 more Smart Citation
“…Zinc-Sodium Hydroxide Method (6).--In this method thc organic iodine is replaced with hydrogen generated iii the nascent form by the reaction of zinc and sodium hydroxide.…”
Section: Methodsmentioning
confidence: 99%
“…Cer-tain of them also show hypotensive activity and are used clinically in the treatment of mild hypertension (2). Several recent papers describe closely related substatices lacking the sulfamoyl group, exemplified by 7-chloro-3-methyl-1,2,4-benzothiadiazine 1,ldioxide (diazoxide) (11), as possessing antihypertensive but not diuretic activity (3)(4)(5)(6).…”
mentioning
confidence: 99%